Comparative Time-Scale Gene Expression Analysis Highlights the Infection Processes of Two Amoebophrya Strains - Farhat, Sarah; Florent, Isabelle; Noel, Benjamin; Kayal, Ehsan; Da Silva, Corinne; Bigeard, Estelle; Alberti, Adriana; Labadie, Karine; Corre, Erwan; Aury, Jean-Marc; Rombauts, Stephane; Wincker, Patrick; et al. (Frontiers in Microbiology, 2018)
Understanding factors that generate, maintain, and constrain host-parasite associations is of major interest to biologists. Although little studied, many extremely virulent micro-eukaryotic parasites infecting microalgae have been reported in the marine plankton. This is the case for Amoebophrya, a diverse and highly widespread group of Syndiniales infecting and potentially controlling dinoflagellates population. Here, we analyzed the time-scale gene expression of a complete infection cycle of two Amoebophrya strains infecting the same host (the dinoflagellate Scrippsiella acuminata), but diverging by their host range (one infecting a single host, the other infecting more than one species). Over two-thirds of genes showed two-fold differences in expression between at least two sampled stages of the Amoebophrya life cycle. Genes related to carbohydrate metabolism as well as signaling pathways involving proteases and transporters were overexpressed during the free-living stage of the parasitoid. Once inside the host, all genes related to transcription and translation pathways were actively expressed, suggesting the rapid and extensive protein translation needed following host-cell invasion. Finally, genes related to cellular division and components of the flagellum organization were overexpressed during the sporont stage. In order to gain a deeper understanding of the biological basis of the host-parasitoid interaction, we screened proteins involved in host-cell recognition, invasion, and protection against host-defense identified in model apicomplexan parasites. Very few of the genes encoding critical components of the parasitic lifestyle of apicomplexans could be unambiguously identified as highly expressed in Amoebophrya. Genes related to the oxidative stress response were identified as highly expressed in both parasitoid strains. Among them, the correlated expression of superoxide dismutase/ascorbate peroxidase in the specialist parasite was consistent with previous studies on Perkinsus marinus defense. However, this defense process could not be identified in the generalist Amoebophrya strain, suggesting the establishment of different strategies for parasite protection related to host specificity.